Life-History Data of a Mexican Population of Triatoma nitida (Hemiptera: Reduviidae). Issue 1 (11th October 2019) - Martínez-Ibarra, J Alejandro; Meraz-Medina, Tzintli; Nogueda-Torres, Benjamin; Villagrán-Herrera, María E; de Diego-Cabrera, Jose A
Abstract: This study reports the third collection of Triatoma nitida Usinger in Mexico, with a brief description of the collection area and an investigation of parameters related to its vectorial capacity. Whether a triatomine (Hemiptera: Reduviidae) species is a primary or secondary vector is determined by factors that include vectorial capacity, anthropophilic habits, geographic distribution, and capacity to invade and colonize human dwellings. However, when the primary vectors are removed, secondary vectors, such as T. nitida, can become important transmitters of Trypanosoma cruzi Chagas to humans. To estimate the vectorial capacity of T. nitida, the egg-to-adult development time, number of blood meals required to molt to the adult stage, accumulative mortality, onset time for feeding, and feeding and defecation times were examined. Triatoma nitida ( n = 100) required a median of 590 d to complete its development time, with a median of 31 blood meals. Almost half (46.5%) of the nymphs died during the cycle. The onset of feeding time exceeded 5 min in all nymphal instars (except on fourth-instar) and adults and feeding times exceeded 22 min in all instars, except on first-instar nymphs. No defecation was observed for 65.6% ( n = 383) of the triatomines during a 30-min observation period. Based on the six parameters, the vectorial capacity of T. nitida should be considered as low. However, surveillance programs should include this species because the potential importance of T. nitida as a vector has been demonstrated in other countries.